Transcriptome sequencing and functional verification revealed the roles of exogenous magnesium in tobacco anti-PVY infection - Guo, Huiyan; Xu, Chuantao; Wang, Fei; Jiang, Lianqiang; Lei, Xiao; Zhang, Mingjin; Li, Rui; Lan, Xinyu; Xia, Zihao; Wang, Zhiping; Wu, Yuanhua (Frontiers in Microbiology, 2023)
Potato virus Y (PVY) infection causes necrosis and curling of leaves, which seriously affect the yield and quality of Solanaceous crops. The roles of nutrient elements in the regulation of plant resistance to virus infection has been widely reported, while the mechanisms are poorly studied. Previous studies in our laboratory have demonstrated that foliar spraying of MgSO4 could induce Nicotiana tabacum resistance to PVY by increasing the activity of defense-related enzymes. Consistent with the results, we found that exogenous magnesium (Mg) had a certain effect on N. tabacum anti-PVY infection. Meanwhile, Illumina RNA sequencing revealed that Mg induced resistance to PVY infection was mainly by regulating carbohydrate metabolism and transportation, nitrogen metabolism, Ca 2+ signal transduction and oxidative phosphorylation. Moreover, we used virus-induced gene silencing assays to verify the function of homologs of five N. tabacum genes involved in above pathways in N. benthamiana. The results showed that NbTPS and NbGBE were conducive to PVY infection, while NbPPases and NbNR were related to resistance to PVY infection. These results suggested a novel strategy for resistance to PVY infection and provided a theoretical basis for virusresistance breeding.